Cheilosia (Diptera, Syrphidae: Rhingiini) of Nepal with descriptions of 29 new species - Barkalov, Anatolij V.; Ståhls, Gunilla (European Journal of Taxonomy, 2022)
The genus Cheilosia (Diptera: Syrphidae: Rhingiini) of Nepal is reviewed. We recorded 37 species of Cheilosia, of which 29 species are described here. Twenty-six of the new species are classified to a subgenus: Cheilosia (Cheilosia) angusta sp. nov., C. (C.) falcata sp. nov., C. (C.) hauseri sp. nov., C. (C.) maculata sp. nov., C. (C.) pica sp. nov., C. (C.) pilivena sp. nov., C. (C.) spinosa sp. nov., C. (C.) spuria sp. nov., C. (C.) weiperti sp. nov., C. (Montanocheila) albipicta sp. nov., C. (M.) alpha sp. nov., C. (M.) brevimontana sp. nov., C. (M.) gilva sp. nov., C. (M.) minuscula sp. nov., C. (M.) nigella sp. nov., C. (M.) pernigra sp. nov., C. (M.) picta sp. nov., C. (Floccocheila) collis sp. nov., C. (F.) crassata sp. nov., C. (F.) illustratoides sp. nov., C. (F.) indistincta sp. nov., C. (F.) leucozonoides sp. nov., C. (F.) vellea sp. nov., C. (Eucartosyrphus) procera sp. nov., C. (Pollinocheila) rava sp. nov., and C. (Taeniochilosia) nepalensis sp. nov. The remaining three new species, C. flavigena sp. nov., C. insolita sp. nov., and C. versa sp. nov., are described based on a female only, and are thus not classified to a subgenus. The subgenus Taeniochilosia Oldenberg, 1916 is here re-defined to also include species with a pilose eye in combination with the previously defined characters. Cheilosia nigriventris Barkalov & Cheng, 2004 is herewith placed as junior synonym of Cheilosia erratica Barkalov & Peck, 1997, and the description of the female sex is provided. We provide digital photographs and line drawings to illustrate morphological details of all species, and an identification key to the subgenera and to the species recorded for Nepal. We explored the infrageneric classification of some Nepalese species new to science for which molecular work was possible using mtDNA COI barcode sequences. A maximum likelihood analysis of the assembled COI barcode dataset with multiple representatives of the most speciose Palearctic subgenera of Cheilosia resolved the included seven taxa from Nepal within subgenera Cheilosia s. str. and Montanocheila Barkalov, 2002. The large number of new species of this study highlights the still prevailing incomplete knowledge of this speciose genus in the montane regions of the Palearctic and Oriental realms.